Pareto: A Great Classic Author of the Future. Overview and Introduction - Lombardinilo, Andrea; Bianco, Adele; Susca, Emanuela (Italian Sociological Review, 2024)
This number of the Italian Sociological Review presents a number of papers emerging from the reflections and debate of the seminar organized in September 2023 by the Universities “G. d’Annunzio” of Chieti-Pescara and “Carlo Bo” of Urbino for the centenary of the death of Vilfredo Pareto. The intention of the organizers and participants in the seminar was not only to commemorate the figure of a classical author on sociology, economy and political science, but also to reflect on the topical nature of his intellectual legacy and on the importance of his teaching for the future.